Governance in stock broking: A study on executors' technical knowledge, self-efficacy and continuous learning and training - Ng, May Yee (2012)
Agency theory posits that firm performance is depending on agents’ competency. Hence, this study investigates whether stock brokers compliant to SG–Rules is achieved due to the competency of the Executors (agent). Executors’ technical knowledge (Tech-know) in the SG–Rules, level of self–efficacy (SE) and their current state of continuous learning and training (CLT) are deemed determinants of stock broker’s compliance. This framework is modelled from the Parker’s (2000) regulatory compliance model. This research deploys both quantitative and qualitative methods. Seventeen hypotheses are dedicated to examine the differences in the level of Tech–know, SE and CLT among various groups of Executors, interaction between these compliance factors, and most importantly their impact on stock brokers’ SG–Rules compliance level. Statistical analyses used in this study include ANOVA, independent-samples t-test and multiple regressions. Qualitative sequential phenomenological study is conducted to seek confirmation on the hypothetical reasons on some of the counter-intuitive empirical findings. Responses gathered are analysed using Giorgi (1985) procedure.